Recent Updates in Female Infertility: A Short Review of Literature - Lata Kanyal Butola; Ranjit Ambad; Anjali Vagga (Institute of Medico-legal Publications Pvt Ltd, 2021)
Infertility is defined as the inability to conceive after 1 year of unprotected intercourse. It has been estimatedthat 93% of healthy couples practicing unprotected intercourse should except to conceive within 1 year.Females presenting after this time should therefore be regarded as possibly infertile and should be evaluated.Although infertility is considered by some as primarily a woman’s problem, men often contribute to and arealso affected. Infertility problem often arise as a result of hormonal dysfunction of the hypothalamic-pituitarygonadal axis. Human infertility is a complex problem, which has numerous consequences depending on thesociety and cultural background, age, hormone problems, environmental problem, gender, lifestyle, sexualhistory, of the people it affects. Infertility is a global public health concern this is partly due to its complexityin etiology as well as difficulty in preventing, diagnosing and treating it.